Length-scale mediated adhesion and directed growth of neural cells by surface-patterned poly(ethylene glycol) hydrogels - Krsko, Peter; McCann, Thomas E.; Thach, Thu-Trang; Laabs, Tracy L.; Geller, Herbert M.; Libera, Matthew R. (Biomaterials, 2009)
We engineered surfaces that permit the adhesion and directed growth of neuronal cell processes but that prevent the adhesion of astrocytes. This effect was achieved based on the spatial distribution of sub-micron-sized cell-repulsive poly(ethylene glycol) [PEG] hydrogels patterned on an otherwise cell-adhesive substrate. Patterns were identified that promoted cellular responses ranging from complete non-attachment, selective attachment, and directed growth at both cellular and subcellular length scales. At the highest patterning density where the individual hydrogels almost overlapped, there was no cellular adhesion. As the spacing between individual hydrogels was increased, patterns were identified where neurites could grow on the adhesive surface between hydrogels while astrocytes were unable to adhere. Patterns such as lines or arrays were identified that could direct the growth of these subcellular neuronal processes. At higher hydrogel spacings, both neurons and astrocytes adhered and grew in a manner approaching that of unpatterned control surfaces. Patterned lines could once again direct growth at cellular length scales. Significantly, we have demonstrated that the patterning of sub-micron/nano scale cell-repulsive features at microscale lengths on an otherwise cell-adhesive surface can differently control the adhesion and growth of cells and cell processes based on the difference in their characteristic sizes. This concept could potentially be applied to an implantable nerve-guidance device that would selectively enable regrowing axons to bridge a spinal-cord injury without interference from the glial scar.